The Hardness Analysis of Epoxy Composite Reinforced with Glass Fiber Compared to Nettle Fibers - I Gede Putu Agus Suryawan; NPG Suardana; IN Suprapta Winaya; IWB Suyasa (International Journal of Engineering and Emerging Technology, 2020)
The purpose of this study is to compare the hardness of glass fiber reinforced composite materials with the hardness of netted fiber-reinforced composite materials. Glass fiber is a commercial fiber that has been used in various industries while nettle fiber is a natural fiber that is more environmentally friendly. Composite material has several advantages, namely the form that can be adjusted, high strength, lightweight and resistant to corrosion. Nettle plants are plants that have strong fibers in the bark. In this study, nettle composites were made with variations in the weight fractions of 10%, 15%, and 20%. Hardness testing used the Shore D Durometer. The results of the hardness value of glass fiber composites with weight fractions of 10%, 15%, and 20% are 82.4 Shore D, 84.5 Shore D, and 86.5 Shore D, show an increase in stable hardness because the glass fiber factor is already commercial, the fiber strength is evenly distributed. The hardness values of nettle fiber composites with fractions of 10%, 15%, and 20% are 81.6 Shore D, 85 Shore D, and 86.6 Shore D, the hardness value of each nettle composite increases with the addition of fiber weight fraction but is unstable due to the strength factor of each nettle single fiber uneven. Furthermore, with the right treatment, nettle fiber can replace glass fiber.